(untitled) (AYUSHDHARA, 2016)
Deterioration in the levels of vital capacity, memory and intellectual abilities are commonly observed in geriatric age group. The prevalence of age related cognitive decline is becoming an important public health concern as there is premature ageing due various environmental and lifestyle changes. According to the surveillance studies 15% people are suffering from moderate to severe cognitive decline/dementia after the age of 65 years. If left unchecked, symptoms most of the times progress into more serious conditions, such as dementia and depression, or even Alzheimer’s disease. Dementia accounts for one of the major disability in older people. Alzheimer’s disease is now recognized as the most common disorder of dementia. Cognitive decline in advanced age make the person handicap for his daily activities of living and pose burden on his family and society. Rasayana in Ayurveda are the drugs which are known to specifically improve the body tissues and possess adaptogenic activity and therefore delay premature ageing process. Some of the Rasayana are specific to brain tissue known as Medhyarasayana. Present article reviews the evidences regarding the efficacy of Ayurveda Medhya rasayana drugs on prevention and management of cognitive decline in advanced age.